2020
DOI: 10.3892/etm.2020.8543
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 activates α‑catenin phosphorylation to inhibit lung cancer cell proliferation and invasion

Abstract: The efficacy of ginsenoside Rh2 (Rh2) in cancer therapy has been reported; however, its function in lung cancer remains unknown. To analyze the role of Rh2 in the inhibition of lung cancer cell proliferation in the present study, protein expression levels of E-cadherin, vimentin, β-catenin, Smo, Gli1, and α-catenin were assessed by western blotting, whilst mRNA expression levels of TCF7 FZD8, Smo, Gli1, Gli2, and Gli3 were determined by reverse transcription-quantitative PCR in the A549 cell line. Phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Mounting evidences showed that FZD8 was involved in various malignant tumors including prostate cancer [ 31 33 ], lung cancer[ 34 ], breast cancer [ 35 ], and gastric cancer[ 36 ]. Yin et al [ 37 ] suggested that FZD8 had an important role in resistance to treatment with cisplatin plus TRAIL in patients triple-negative breast cancer, thus making it a potential target for chemosensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidences showed that FZD8 was involved in various malignant tumors including prostate cancer [ 31 33 ], lung cancer[ 34 ], breast cancer [ 35 ], and gastric cancer[ 36 ]. Yin et al [ 37 ] suggested that FZD8 had an important role in resistance to treatment with cisplatin plus TRAIL in patients triple-negative breast cancer, thus making it a potential target for chemosensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidences showed that FZD8 was involved in various malignant tumors including prostate cancer [31][32][33], lung cancer [34], breast cancer [35], and gastric cancer [36]. Yin et al [37] suggested that FZD8 had an important role in resistance to treatment with cisplatin plus TRAIL in patients triple-negative breast cancer, thus making it a potential target for chemosensitization.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that Rh1 inhibited the proliferation of A549 cells by suppressing the Wnt signaling pathway. Zhang, et al [13] found that ginsenoside Rh2 (Rh2) significantly up-regulated E-cadherin expression and downregulated the expression of vimentin, suggested that Rh2 inhibited A549 cells proliferation. Rh2 also suppressed key Wnt signaling genes, Wnt3, TCF7 and FZD8, and hedgehog signaling genes, Smo, Gli1, Gli2 and Gli3.…”
Section: Effect Of Ginsenosides On Cell Proliferation Of Lung Cancer Cellsmentioning
confidence: 99%